Behaviour of geochronometers and timing of metamorphic reactions during deformation at lower crustal conditions: phase equilibrium modelling and U–Pb dating of zircon, monazite, rutile and titanite from the Kalak Nappe Complex, northern Norway. (29th April 2015) - Gasser, D.; Jeřábek, P.; Faber, C.; Stünitz, H.; Menegon, L.; Corfu, F.; Erambert, M.; Whitehouse, M. J.
Abstract This study investigates the behaviour of the geochronometers zircon, monazite, rutile and titanite in polyphase lower crustal rocks of the Kalak Nappe Complex, northern Norway. A pressure–temperature–time–deformation path is constructed by combining microstructural observations with P–T conditions derived from phase equilibrium modelling and U–Pb dating. The following tectonometamorphic evolution is deduced: A subvertical S1 fabric formed at 730–775 °C and 6.3–9.8 kbar, above the wet solidus in the sillimanite and kyanite stability fields. The event is dated at 702 ± 5 Ma by high‐U zircon in a leucosome. Monazite grains that grew in the S1 fabric show surprisingly little variation in chemical composition compared to a large spread in (concordant) U–Pb dates from c. 800 to 600 Ma. This age spread could either represent protracted growth of monazite during high‐grade metamorphism, or represent partially reset ages due to high‐T diffusion. Both cases imply that elevated temperatures of >600 °C persisted for over c. 200 Ma, indicating relatively static conditions at lower crustal levels for most of the Neoproterozoic. The S1 fabric was overprinted by a subhorizontal S2 fabric, which formed at 600–660 °C and 10–12 kbar. Rutile that originally grew during the S1‐forming event lost its Zr‐in‐rutile and U–Pb signatures during the S2‐forming event. It records Zr‐in‐rutile temperatures of 550–660 °C and Caledonian ages of 440–420 Ma. Titanite grew at the expense of rutile at slightly lower temperatures of 550 °C during ongoing S2 deformation; U–Pb ages of c. 440–430 Ma date its crystallization, giving a minimum estimate for the age of Caledonian metamorphism and the duration of Caledonian shearing. This study shows that (i) monazite can have a large spread in U–Pb dates despite a homogeneous composition; (ii) rutile may lose its Zr‐in‐rutile and U–Pb signature during an amphibolite facies overprint; and (iii) titanite may record crystallization ages during retrograde shearing. Therefore, in order to correctly interpret U–Pb ages from different geochronometers in a polyphase deformation and reaction history, they are ideally combined with microstructural observations and phase equilibrium modelling to derive a complete P–T–t–d path.